Action-rule-based cognitive control enables efficient execution of stimulus–response conflict tasks: a model validation of Simon task performance - Otani, Yoshitaka; Katagiri, Yoshitada; Imai, Emiko; Kowa, Hisatomo (Frontiers in Human Neuroscience, 2023)
Introduction: The human brain can flexibly modify behavioral rules to optimize task performance (speed and accuracy) by minimizing cognitive load. To show this flexibility, we propose an actionrule-based cognitive control (ARC) model. The ARC model was based on a stochastic framework consistent with an active inference of the free energy principle, combined with schematic brain network systems regulated by the dorsal anterior cingulate cortex (dACC), to develop several hypotheses for demonstrating the validity of the ARC model.Methods: A step-motion Simon task was developed involving congruence or incongruence between important symbolic information (illustration of a foot labeled "L" or "R," where "L" requests left and "R" requests right foot movement) and irrelevant spatial information (whether the illustration is actually of a left or right foot). We made predictions for behavioral and brain responses to testify to the theoretical predictions.Results: Task responses combined with event-related deep-brain activity measures demonstrated a key contribution of the dorsal anterior cingulate cortex (dACC) in this process and provided evidence for the main prediction that the dACC could reduce the Shannon surprise term in the free energy formula by internally reversing the irrelevant rapid anticipatory postural adaptation (APA). We also found sequential effects with modulated dip depths of event-related deep-brain activity (ER-DBA) waveforms that support the prediction that repeated stimuli with the same congruency can promote remodeling of the internal model through the information gain term while counterbalancing the surprise term. Discussion: Overall, our results were consistent with experimental predictions, which may support the validity of the ARC model. The sequential effect accompanied by dip modulation of ER-DBA 2 This is a provisional file, not the final typeset article waveforms suggests that cognitive cost is saved while maintaining cognitive performance in accordance with the framework of the ARC based on 1-bit congruency-dependent selective control.